Pengaruh Konten Marketing Dan Citra Merek Terhadap Keputusan Pembelian Dengan Dimediasi Minat Beli Pada Pengguna Aplikasi Shopee (International Forum of Researchers and Lecturers, 2024)
The digital age is evolving quickly right now. The surge in electronic transactions has also caused customers to migrate to online shopping, specifically e-commerce. Customers are interested in purchasing when engaging marketing content is available, and they are also less likely to hesitate when purchasing from well-known brands. This study looks at factors related to content marketing, brand perception, decisions, and purchases that are influenced by purchase intention. Data was gathered via a Google Form survey from 100 respondents. analysis of data with the SEM smartPLS 3.0 program. The study's findings indicate that while brand image has no effect on decisions to buy, marketing content does affect interest and interest in buying influences decisions to buy. Purchase interest is not a mediator between decisions and the impact of marketing information.